1987
DOI: 10.1139/f87-140
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Complexation and pH on Individual and Combined Heavy Metal Toxicity to a Freshwater Green Alga

Abstract: The effect of complexation and pH on heavy metal (Cu, Zn, Pb) toxicity to a freshwater green alga, Scenedesmus quadricauda, was investigated. Extracellular ligands produced by S. quadricauda were capable of binding heavy metals and reducing their single and combined toxicities. Apparent complexing capacities and the ability of the sediment humics and artificial complexing agents such as ethylenediaminetetraacetic acid (EDTA), citric acid, and glycolic acid to ameliorate Cu, Zn, or Pb toxicity were also assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…The newly-formed iron hydroxides have large surface areas and can bind orthophosphate, thereby limiting phosphorus availability to phytoplankton (Kopacek et al, 2005). In addition, organically-bound Al and other heavy metals may also be liberated by irradiation and may reach toxic levels (Starodub et al, 1987;Kopacek et al, 2005). Winch et al (2002) found that as UVB exposure time increased, DOC concentrations declined and toxicity of some metals to Selenastrum subcapitata increased.…”
Section: Discussionmentioning
confidence: 99%
“…The newly-formed iron hydroxides have large surface areas and can bind orthophosphate, thereby limiting phosphorus availability to phytoplankton (Kopacek et al, 2005). In addition, organically-bound Al and other heavy metals may also be liberated by irradiation and may reach toxic levels (Starodub et al, 1987;Kopacek et al, 2005). Winch et al (2002) found that as UVB exposure time increased, DOC concentrations declined and toxicity of some metals to Selenastrum subcapitata increased.…”
Section: Discussionmentioning
confidence: 99%
“…Metal pollution in aquatic systems is related to pH, i.e., when the pH of water decreases, the solubility and speciation of metals are enhanced thus increasing their toxicity (Campbell and Stokes, 1985;Starodub et al, 1987;Rai et al, 1993). Arsenic, cadmium, copper, lead, and mercury are the most common heavy metal contaminants.…”
Section: Metalsmentioning
confidence: 99%
“…Those released by phytoplankton and bacteria have been the most studied (McKnight and Morel, 1980;Jardim and Pearson, 1984;Mittelman and Geesey, 1985;Starodub et al, 1987;Xue and Sigg, 1990;Geesey et al, 1992;Leppard, 1995;Myklestad, 1995;Humble et al, 1997). The quantity and quality of extracellular products are dependent upon species, growth phase, physiological conditions and nutrient concentrations, making generalisations difficult.…”
Section: 434mentioning
confidence: 99%